3 Uspio-enhanced magnetic resonance coronary angiography compared to computed tomography coronary angiography. (15th May 2019) - Daghem, Marwa; Ramaesh, Rishi; Macnaught, Gillian; Dweck, Marc R; Semple, Scott; Beek, Edwin JR van; Newby, David E; Williams, Michelle C
Abstract : Background: Recent concerns regarding gadolinium has led to the investigation of alternatives for magnetic resonance coronary angiography (MRCA) including non-contrast imaging and contrast imaging with ultrasmall superparamagnetic particles of iron oxide (USPIO). Methods: Seven patients underwent USPIO-enhanced MRCA using a 3 Tesla PET/MRI scanner and computed tomography (CT) coronary angiography (CTCA) using a 128-multidetector computed tomography (CT) scanner. MRCA was performed using FLASH magnetic resonance angiography sequences with 3 to 4 mg/kg of intravenous ferumoxytol. Image analysis was performed by two observers blinded to other imaging. Per segment image quality was rated on a 4-point scale. Per vessel coronary assessment was performed, with segments classified as less than or greater than 50% luminal diameter. Results: 99 segments in 7 patients were assessed. Diagnostic image quality was observed in 80% (79/99) of segments with USPIO-enhanced MRCA compared to 99% (98/99) with CCTA. 85 segments in 21 vessels were available for the assessment of stenoses. On CCTA, 12 segments in 8 vessels had one or more >50% stenosis. Per vessel diagnostic accuracy of USPIO-enhanced MRCA was good with sensitivity 63%, specificity 77%, positive predive value (PPV) 63%, negative predictive value (NPV) 77%, and accuracy 71%, and was better for proximal compared to distal segments. Conclusion: USPIO-enhanced MRCA has a good image quality for the identification of vessel segments and stenoses, particularly in proximal segments.